Tuck everlasting - Babbitt, Natalie (New York : Farrar Straus and Giroux, 1985)
The Tuck family is confronted with an agonizing situation when they discover that a ten-year-old girl and a malicious stranger now share their secret about a spring whose water prevents one from ever growing any older.
"A Sunburst book.".
Elem. School Library Collection.
School Library Journal.
Wilson's Children.
5.9.
5.9
Keywords: Fantasy; Fantastic fiction